Assessment of regeneration of bone in the extracted third molar sockets augmented using xenograft (CollaPlugTN Zimmer) in comparison with the normal healing on the contralateral side - Murugan Ranganathan; M Balaji; R Krishnaraj; Vivek Narayanan; Annamalai Thangavelu (Wolters Kluwer Medknow Publications, 2017)
Introduction: Alveolar bone resorption is a significant clinical problem. Bone loss in third molar region following extraction or surgical removal not only leads to periodontal problems in second molar region but also it may lead to some serious problems like increased incidence of angle fractures. In order to reduce the risks following third molar surgery, the socket should be augmented with bone grafts. In recent days guided tissue regeneration is the most accepted and successful technique followed many authors and its efficacy has been proved. Materials and Methods: Based upon our clinical experience, the use of bio absorbable collagen wound dressing such as CollaPlugTN has achieved quick healing and more primary wound coverage. Amongst the graft materials collagen is preferable due to its high biocompatibility and hemostatic ability. This study was done to assess the regeneration of bone in the extracted third molar sockets using xenograft (CollaPlugTN-Zimmer) which was compared with the normal healing on the contra lateral side. The assessment was done to analyze post-operative healing complications and to compare the bone density formed between control site and implant site radiologically. Conclusion: On this basis of this study, the use of collaplugTN appears to be beneficial to the patient in postoperative wound healing and also for better bone formation. The use of this material was advantageous because of its simplicity of application cost effectiveness and availability. There is enhanced wound healing and early bone formation.